Polyoxygenated Diterpene Produced by The Indonesian Marine Sponge Callyspongiasp. as an Inhibitor of the Human Pancreatic Cancer Cells - VIQQI KURNIANDA; SUCI FARADILLA; SOFYATUDDIN KARINA; SRI AGUSTINA; MARIA ULFAH; CHITRA OCTAVINA; FARAH SYAHLIZA; MUHAMMAD RIZKI RAMADHAN; SYAHRUL PURNAWAN; MUSRI MUSMAN (Microbiology Indonesia, 2019)
The bioactive compound from the Indonesian Marine SpongeCallyspongia sp.isolated based on bioassay-guided separation with several steps of chromatography has been done. There are 4 major compound known as isocopalane diterpene derivatives together with a plausible new compound, isocopalanol, a polyoxygenated isocopalane diterpene. Isocopalanol has molecular weight [M+H]+ 412.576 m/z indicate that the compound has molecular formula C24H44O5 determined by LCMS-ESI. This compound has bioactivity IC50 = 0.1 Î¼g / mL against human pancreatic cancer cell.Â